Epizooty of Tularemia, Detected in the Population of the Common Vole in the Natural Focus of Steppe Type in the South-East of the Rostov Region in 2020 - M. V. Zabashta; N. L. Pichurina; A. P. Khametova; A. V. Zabashta; I. V. Orekhov; O. P. Dobrovol’sky; V. V. Stakheev; E. S. Fomina; E. V. Kovalev; A. V. Fedchenko; A. K. Noskov; М. В. Забашта; et al. (Problems of Particularly Dangerous Infections, 2022)
The aim of study was to conduct epizootiological monitoring of natural tularemia foci of the steppe type and investigate epizootic activity in the south-east of the Rostov Region.Materials and methods. An epizootiological survey was carried out on the territory of Remontnensky, Sal’sky and Peschanokopsky districts of the Rostov Region in 2019–2021. To capture and collect mammals, Ixodidae ticks and to study the samples of field material conventional methods were used.Results and discussion. Habitation of 16 species of small mammals, 6 species of Ixodidae ticks has been found. Molecular-genetic analysis of the voles has revealed the presence of the species Microtus arvalis obscurus in the studied area of the region. The circulation of the tularemia agent has been established in the population of common and social voles, forest mouse, hare, rook, Dermacentor marginatus, Hyalomma marginatum, removed from rooks. In May 2020, a high increase in the number of the social vole in the Remontnensky district (up to 21 %), in July 2020 – the common vole in the agrocenoses of the Sal’sky district (up to 33 %) was observed. An extensive epizooty of tularemia was detected in the population of common vole in the south-east of the Rostov Region and in adjacent territories in the Republic of Kalmykia and the Stavropol territory. Two cultures of the pathogen were isolated from the fallen and captured social voles, and four cultures – from the common vole. The isolated strains belong to the Holarctic subspecies of Francisella tularensis EryR. The results obtained attest to the activation of the natural tularemia focus in the south-east of the Rostov Region and its high epizootic activity. Цель исследования – проведение эпизоотологического мониторинга природных очагов туляремии степного типа и изучение эпизоотической активности на юго-востоке Ростовской области.Материалы и методы. Эпизоотологическое обследование проведено в 2019–2021 гг. на территории Ремонтненского, Сальского и Песчанокопского районов Ростовской области. При ...